The effect of adjuvant radiotherapy on overall survival in adults with intracranial ependymoma. Issue 4 (19th December 2019) - Prabhu, Roshan S; Corso, Christopher D; Ward, Matthew C; Heinzerling, John H; Dhakal, Reshika; Buchwald, Zachary S; Patel, Kirtesh R; Asher, Anthony L; Sumrall, Ashley L; Burri, Stuart H
Abstract: Background: Adult intracranial ependymoma is rare, and the role for adjuvant radiotherapy (RT) is not well defined. Methods: We used the National Cancer Database (NCDB) to select adults (age ≥ 22 years) with grade 2 to 3 intracranial ependymoma status postresection between 2004 and 2015 and treated with adjuvant RT vs observation. Four cohorts were generated: (1) all patients, (2) grade 2 only, (3) grade 2 status post–subtotal resection only, (4) and grade 3 only. The association between adjuvant RT use and overall survival (OS) was assessed using multivariate Cox and propensity score matched analyses. Results: A total of 1787 patients were included in cohort 1, of which 856 patients (48%) received adjuvant RT and 931 (52%) were observed. Approximately two-thirds of tumors were supratentorial and 80% were grade 2. Cohorts 2, 3, and 4 included 1471, 345, and 316 patients, respectively. There was no significant association between adjuvant RT use and OS in multivariate or propensity score matched analysis in any of the cohorts. Older age, male sex, urban location, higher comorbidity score, earlier year of diagnosis, and grade 3 were associated with increased risk of death. Conclusions: This large NCDB study did not demonstrate a significant association between adjuvant RT use and OS for adults with intracranial ependymoma, including for patients with grade 2 ependymoma status post–subtotal resection. The conflicting results regarding the efficacy of adjuvant RT in this patient population highlight the need for high-quality studies to guide therapy recommendations in adult ependymoma.